Welding procedures of Turbine Blades by Using ER 309L Austenitic Filler Wire - A.H. Fadhil; S. A. Emad; K.H. Abbas; H. A. Olaa (Engineering and Technology Journal, 2017)
In the present work it has been investigated the repair of LP-blades steam turbine made of AISI 410 martensitic stainless steels (MSS) by GTAW welding, the repair welding carried out by using ER 309L as consumable filler wire. PWHT was carried out at 1100ᵒC for 1h. The structure-property relationships of the weldments were established based on the current modes employed by utilizing combined techniques of optical microscopy, line/point and EDS analysis. Results showed that Micro-hardness along the base and HAZ regions increased after PWHT as compared to in state of as-welded. After welding process, microstructure photographs of weld-metal region revealed two phase the vermicular δ-Ferrite and γ-austenite matrix. HAZ region consisted of tempered lath martensite with carbides. Line/Point analysis revealed the direction of segregation, whereas chromium was increased in core and depleted in boundary, while nickel was depleted in core and increased in boundary, this support the δ – ferrite was primarily solidified.